The politics of COVID-19: Differences between U.S. red and blue states in COVID-19 regulations and deaths - C. Dominik Güss; Lauren Boyd; Kelly Perniciaro; Danielle C. Free; J.R. Free; Ma. Teresa Tuason (Elsevier, 2023)
The study investigated infection variables and control strategies in 2020 and 2021 and their influence on COVID-19 deaths in the United States, with a particular focus on comparing red (Republican) and blue (Democratic) states. The analysis reviewed cumulative COVID-19 deaths per 100,000 by year, state political affiliation, and a priori latent factor groupings of mitigation strategies (lockdown days in 2020, mask mandate days, vaccination rates), social demographic variables (ethnicity, poverty rate), and biological variables (median age, obesity). Analyses first identified possible relationships between all assessed variables using K-means clustering for red, blue, and purple states. Then, a series of regression models were fit to assess the effects of mitigation strategies, social, and biological factors specifically on COVID-19 deaths in red and blue states. Results showed distinct differences in responding to COVID infections between red states to blue states, particularly the red states lessor adoption of mitigation factors leaving more sway on biological factors in predicting deaths. Whereas in blue states, where mitigation factors were more readily implemented, vaccinations had a more significant influence in reducing the probability of infections ending in death. Overall, study findings suggest politicalization of COVID-19 mitigation strategies played a role in death rates across the United States.